Association of Serum Anti-PCSK9 Antibody Levels with Favorable Postoperative Prognosis in Esophageal Cancer - Ito, Masaaki; Hiwasa, Takaki; Oshima, Yoko; Yajima, Satoshi; Suzuki, Takashi; Nanami, Tatsuki; Sumazaki, Makoto; Shiratori, Fumiaki; Funahashi, Kimihiko; Li, Shu-Yang; Iwadate, Yasuo; Yamagata, Hiroki; et al. (Frontiers in Oncology, 2021)
Background Esophageal cancer often appears as postoperative metastasis or recurrence after radical surgery. Although we had previously reported that serum programmed cell death ligand 1 (PD-L1) level correlated with the prognosis of esophageal cancer, further novel biomarkers are required for more precise prediction of the prognosis. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is associated with the cholesterol metabolism. But there was no report of relationship between serum PCSK9 antibody and cancer. Therefore, we investigated whether anti-PCSK9 antibodies could be a novel biomarker for solid cancer. Methods Serum levels of anti-PCSK9 antibodies and antigens in patients with solid cancer were analyzed using amplified luminescence proximity homogeneous assay-linked immunosorbent assay (AlphaLISA). The reactivity of serum antibodies against recombinant PCSK9 protein was investigated by Western blotting, and the expression of PCSK9 antigens in esophageal cancer tissues was examined by immunohistochemical staining. Results AlphaLISA showed that serum anti-PCSK9 antibody (s-PCSK9-Ab) levels were significantly higher in patients with esophageal cancer, gastric cancer, colorectal cancer, lung cancer, and breast cancer than in healthy donors, and patients with esophageal cancer had the highest levels. There was no apparent correlation between s-PCSK9-Ab and PCSK9 antigen levels. Immunohistochemical staining demonstrated the expression of PCSK9 antigen in both the cytoplasm and nuclear compartments of esophageal squamous cell carcinoma tissue but not in normal tissue. Compared with patients with low s-PCSK9-Ab levels, those with high s-PCSK9-Ab levels had a favorable postoperative prognosis after radical surgery for esophageal cancer. In the multivariate analysis, tumor depth and s-PCSK9-Ab level were identified as independent prognostic factors. In the univariate analysis of clinicopathological features, high PCSK9 antibody levels were not associated with sex, age, location, tumor depth, lymph node status, squamous cell carcinoma antigen, or p53-Ab, whereas they correlated significantly with PD-L1 levels, which were associated with unfavorable prognosis. Correlation between s-PCSK9-Ab and PD-L1 levels was also confirmed in the logistic regression analysis; therefore, low s-PCSK9-Ab levels could discriminate another poor prognosis group other than high-PD-L1 group. Conclusions Patients with solid cancer had higher s-PCSK9-Ab levels than healthy donors. High s-PCSK9-Ab levels indicated better prognosis for overall survival after surgery in patients with esophageal cancer.